Development of self balancing platform on mobile robot using PID controller - Mat Ali, Mazita (2013)
This thesis presents a development self-balancing platform mobile robot using PID controller. The platform has been designed using mobile robot kits including IMU and two servos, and controlled by an open source microcontroller with PID. An Arduino microcontroller, hobby grade servos, and a two-degree of freedom (axis) accelerometer and gyroscope have been used to create the controlled platform. The controller has been designed to maintain the platform at an initially selected angle when the support structure orientation changes. By using Matlab, the value of PID parameters i.e , Kp, Ki and Kd have been obtained and applied to the arduino. The software has been written with logic to convert the digital data from the accelerometer to an acceleration magnitude vector. The magnitude is then compared to a predetermined mathematical function to infer the angle of tilt of the platform. The angle of tilt is then converted to angle of rotation for the servos to act on. Experiment shows that the platform performed as expected. Overall, the platform design is validated based on the positional accuracy of the platform given the relatively low quality components used to create it.